EFFECTIVENESS OF PRE-OPERATIVE BOWEL PREPARATION VS NO BOWEL PREPARATION ON OUTCOMES OF PEDIATRIC COLORECTAL SURGERIES (Journal of Medical & Health Sciences Review, 2025)
Objective: To compare the effectiveness of pre-operative bowel preparation vs no bowel preparation on outcomes of pediatric colorectal surgeries.Study Design: Randomized control trialPlace and duration of study: The study was conducted at the Department of Pediatric Surgery, Holy Family Hospital, Rawalpindi in the duration from 30 August, 2024 to 22 June, 2025.Methodology: After approval from the ethical committee, 62 patients fulfilling the inclusion criteria were enrolled in this study from outpatient department. All participants were examined physically in person by the primary investigator. After which the patients were divided randomly into two groups A and B, 31 patients in each group. Group A patients were undergone bowel preparation while group B patients were not undergone bowel preparation. All patients were operated by a single consultant pediatric surgeon with more than 10 years of experience. Patients were called for follow up weekly till 6 weeks. Hospital stay was noted at the time of discharge. Wound infection rate was assessed till 30th post-operative day while anastomotic leak was ruled out on clinical and radiologic exam if symptoms were present. All the data of this study were analyzed in SPSS version 26.Results:  We found mean age of patients was 7.18±3.09 years with 48.4% patients were male and 51.6% patients were female. We also found mean hospital stay in bowel preparation group and no bowl preparation group was (6.16±1.57 days vs 5.77±1.43, p=0.315), surgical site infection (16.1% vs 12.9%, p=0.718) and also the anastomotic leak found as (6.5% vs 3.2%, p=0.554). Both groups were showed non-significant results.Conclusion: We concluded that there is no significant difference in surgical outcomes between the group receiving the bowel preparation versus the group not receiving the bowel preparation in terms of surgical site infection rate, anastomotic leak and length of hospital stay.